Storytelling through the Tik Tok Application Affects Followers’ Behaviour Changes - Triwidyati, Endang; Pangastuti, Ria Lestari (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
Storytelling is an art that is becoming a trend on social media, nowadays it is starting to be abandoned by switching to story style uploaded via Facebook, Instagram and Tiktok, which have more fans and followers because the story style is clear and solid. Storytelling through the media is a means of influencing audience affection. The storytelling content conveyed includes an event, experience, or inspirational story that is shared by a Tik Tok account owner to his/her followers. This study aims to examine the storytelling through the Tiktok application affects followers’ behavior changes. The method used in this study is a qualitative method in which the research data is in the form of information obtained from followers of the Tiktok application related to the context discussed in the video in the Tiktok application. The method of determining the sample of purposive informants is done by determining the research informants deliberately based on predetermined criteria. The result of the storytelling data is the process of building a story that is easily understood and understood successfully to convince the audience that there is value in an action plan that can be carried out. The story is supported by facts and appropriate analysis data. Based on the results obtained from this study, it was found that storytelling was effective in conveying messages of positive change and as it was, there was no fraud or engineering to the followers and came up with very creative ideas.